Methods of regional zoning of territories by zones with the risk of landslides - Pozdysheva, Olga; Taldykina, Valeria; Polezhaeva, Elena (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
one of the most important parts of the general complex for studying the regime of landslide processes are geodetic measurements of the development of landslide displacements. Therefore, the justification of the necessary accuracy of geodetic measurements, the choice of the method of such observations and the development of technology for their implementation should proceed from the principle of obtaining the most complete and reliable information about the landslide slope. This article is the result of studying the possibility of using geodetic systems in the research of landslide processes. Methods of investigation of the stress-strain state of rocks of the landslide slope are considered. There are many options for building maps of dangerous areas. The advantages and disadvantages of each method are described.